Understanding terrorism in the age of global media: a communication approach - Archetti, Cristina (Palgrave Macmillan, 2013)
Introduction: a different perspective on terrorism -- The problems with terrorism research -- Terrorism, communication, and the media -- A communication approach -- Explaining radicalisation -- The role of narratives -- The Al Qaeda narrative as a brand -- The way forward